Business Incubators, Accelerators, and Performance of Technology-Based Ventures: A Systematic Literature Review - Leitão, João (2022)
This review aims to identify the typologies of business incubators (BI) and business accelerators (BA) and to define a taxonomy integrating both the BI’s and BA’s characteristics and services portfolio, facilitating the adoption of open innovation practices. A systematic literature review (SLR) was carried out encompassing the research topic concerning the relationship between the incubation structures and the performance of technology-based ventures. This comprehensive SLR encompasses a total of 1614 publications, aiming to advance the knowledge on BI and BA. This SLR allowed for the identification of current trends and future challenges, as well as of the most important authors, publications, and journals in this research framework. This SLR establishes a new taxonomy for BI and BA, based upon three main pillars: human capital, social capital, and organizational capital. BI and BA help in the development of new high-technology ventures, by being facilitators for open innovation practices. This SLR is limited by the literature, as the collection of publications was performed exclusively through ISI Web of Science (WoS). Further research can be made into the modes of how these structures impact open innovation practices at the regional level using a knowledge spillover approach.